PEOPLE’S SATISFACTION WITH THE TRAFFIC PROBLEMS SOLVING IN BANGKOK - Netithanakul, Ardyuth; สกุลสุขเจิญ, สิทธิพันธ์; สอนศิริ, ปวิช; แสงอาทิตย์, ธนาวัฒน์; กัญญาราช, ธนานันต์ (Thai Interdisciplinary and Sustainability Review, 2023)
The objectives of this study were 1) to study people’s satisfaction on solving traffic problems in Bangkok and 2) to compare level of satisfaction on solving traffic problems in Bangkok by personal factors. This study was a quantitative study using a questionnaire distribution method. The population was people who driving a car in Bangkok 1,000 persons. In the analysis and calculation, basic statistics, such as percentage, mean, standard deviation, t-test and F-test, were used. The results revealed that 1) people’s satisfaction with solving traffic problems in Bangkok was at a moderate level. When considering in each aspect, it was found that the most people’s satisfaction was public policy, followed by traffic infrastructure, traffic laws, driving behaviors, and traffic police, respectively. 2) When comparing people’s satisfaction on solving traffic problems in Bangkok, the difference in age, education, occupation, income, kind of using car, and time to use the car resulting in differences of the level of people’s satisfaction on solving traffic problems in Bangkok at significant level at.05.